Correction: Freitas, A.; Pires, J. Investigating the Impact of Topology and Physical Impairments on the Capacity of an Optical Backbone Network. Photonics 2024, 11, 342 - Alexandre Freitas; João Pires (Photonics)
In the original publication [...]